Komparasi Sistem Remunerasi Pada Tiga Perguruan Tinggi Negeri Badan Hukum (PTNbh) - Astridina, Astridina; Maarif, M. Syamsul; Wijayanto, Hari (IPB University, 2017)
ABSTRACTThe research objective is to analyze the suitability of the design of the remuneration system in three PTNbh with preparation stages and principles of remuneration and evaluate the system of socialization and information systems used in the application of the remuneration of the three PTNbh. This research was conducted in three PTNbh located in Jakarta (PTNbh X), West Java (PTNbh Y) and East Java (PTNbh Z) using primary data obtained from in-depth interviews and secondary data derived from the literature, previous research, laws and regulations, government regulations and decrees that are relevant to the implementation of the remuneration of PTNbh. This study used a descriptive approach qualitative analysis benchmarking method. In the preparation of the remuneration system, which first assigned PTNbh not follow the stages of preparation with good remuneration, whereas previously PTNbh derived from State BLU more likely to obey the principle and the preparation of their remuneration has been prepared in detail based on the principles of remuneration and government regulations.ABSTRAKPenelitian ini bertujuan untuk menganalisis kesesuaian rancangan sistem remunerasi di tiga PTNbh dengan tahapan dan prinsip penyusunan remunerasi dan mengevaluasi sistem sosialisasi serta sistem informasi yang digunakan dalam penerapan remunerasi pada tiga PTNbh. Penelitian ini dilakukan di tiga PTNbh yang berada di DKI Jakarta (PTNbh X), Jawa Barat (PTNbh Y) dan Jawa Timur (PTNbh Z) dengan menggunakan data primer yang diperoleh dari wawancara mendalam serta data sekunder yang berasal dari studi pustaka, penelitian terdahulu, peraturan pemerintah yang berlaku dan surat keputusan yang relevan dengan penerapan remunerasi pada PTNbh. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan metode analisis patok duga. Dalam penyusunan sistem remunerasi, PTNbh yang lebih dulu ditetapkan belum mengikuti tahapan penyusunan remunerasi dengan baik, sedangkan PTNbh yang sebelumnya berasal dari PTN BLU cenderung lebih taat azas dan penyusunan remunerasinya sudah disusun dengan detil berdasarkan prinsip-prinsip remunerasi dan peraturan pemerintah.